The effect of polysaccharides krestin bioactivity from coriolus versicolor to estradiol levels on Mus musculus estrous cycle - Sri Puji Astuti Wahyuningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2016)
This study aimed to determine the activity of polysaccharide krestin (PSK) from Coriolus versicolor extract to the dura-tion of estrous cycle and estradiol levels. PSK was administrated for 24 days in female Mus musculus, strain Balb/C, 10 weeks old, weight about 25-30 grams. Polysaccharide krestin given in sub-chronic dose. There were 4 groups, i.e K0 (0 mg/kg BW), P1 (15 mg/kg BW), P2 (30 mg/kg BW), and P3 (60 mg/kg BW). Each treatment group contained 7 replica-tions. Data were analyzed using One Way ANOVA and Duncan test at α = 5%. The duration of estrous cycle was de-termined by vaginal smear methods. The estradiol levels were measured using ELISA kit. The results show that the administration of PSK decreased the duration of estrous cycle with an average of 4.4 days. Polysaccharide krestin dose of 15 and 60 mg/kg BW did not affect the estradiol levels. Decrease of estrous cycle duration was still in the range of normal estrous time between 4-6 days. PSK dose of 15 and 60 mg/kg BW can be used as a therapeutic dose.